Direct intracerebral delivery of a miR-33 antisense oligonucelotide into mouse brain increases brain ABCA1 expression. (26th June 2015) - Jan, Asad; Karasinska, Joanna M.; Kang, Martin H.; de Haan, Willeke; Ruddle, Piers; Kaur, Achint; Connolly, Colum; Leavitt, Blair R.; Sorensen, Poul H.; Hayden, Michael R.
Highlights: Mir-33 inhibition in cultured neurons and glia by an ASO increases ABCA1 expression. Mir-33 ASO treatment leads to enhanced cholesterol and ApoE secretion by astrocytes. Intracerebral-icv infusion of a miR-33 ASO increases ABCA1 expression in mouse brain. Abstract: The ATP-binding cassette transporter A1 (ABCA1) is a membrane bound protein that serves to efflux cholesterol and phospholipids onto lipid poor apolipoproteins during HDL biogenesis. Increasing the expression and activity of ABCA1 have beneficial effects in experimental models of various neurologic and cardiovascular diseases including Alzheimer's disease. Despite the beneficial effects of liver X receptor (LXR) agonists – compounds that increase ABCA1 expression – in preclinical studies, their therapeutic utility is limited by systemic adverse effects on lipid metabolism. Interestingly, microRNA-33 (miR-33) inhibition increases ABCA1 expression and activity in rodents and non-human primates without severe metabolic adverse effects. Herein, we demonstrate that treatment of cultured mouse neurons, astrocytes and microglia with an antisense oligonucelotide (ASO) targeting miR-33 increased ABCA1 expression, which was accompanied by increased cholesterol efflux and apoE secretion in astrocytic cultures. We also show that intracerebral delivery of an ASO targeting miR-33 leads to increased ABCA1 expression in cerebral cortex or subcortical structures such as hippocampus. These findings highlight an effective strategy for increasing brain ABCA1 expression/activity for relevant mechanistic studies.